(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: To assess the efficacy of pterygium excision and conjunctival autograft surgery among patients underwent autologous blood clot or using sutures (10-0 monofilament nylon). Materials and methods: A randomized controlled trial was done at Department of Ophthalmology, Chittagong Medical College Hospital, with a study period from February 2017 to November 2018 was conducted with 60 eyes from 60 patients having primary nasal pterygium. They were selected according to inclusion and exclusion criteria and randomized into two groups for conjunctival autograft. Group A (30) was treated with autologous blood clot and Group B (30) was treated with sutures (10-0 monofilament nylon). All surgeries were performed by a single surgeon at single center. Standard examinations were performed preoperatively and postoperatively, preoperative and postoperative outcomes were evaluated and compared statistically where follow up was done at 1st day,7th days, 1-month, 3-month, and 6-month post operation. The mainoutcome variables were postoperative discomfort, graft stability and complications. Results: This study included 60 patients (60 eyes) with a mean age of 46.77±7.04 (SD) (Range 33 to 58 years) in Group A (30) and 46.17±7.53 (SD) (Range 22 to 58 years) in Group B (30). In Group A, male was 22 (73.3%) and female was 8 (26.7%) where Group Bcontained male 20 (66.7%) and female 10 (33.3%). Follow-up at 1st and 7th post operation days showed marked discomfort in Group B (Mean rank 41.82 and 40.62) compared to Group A (Mean rank 19.18 and 20.38) respectively (p<0.001). At 1st post operation day there were 3 (10%) graft retraction in Group Aonly. Within 6 months follow-up, all grafts were stable and there wasonly 1 (3.3%) granuloma in Group B. Conclusion: In primary pterygium excision, autologous blood clot showed excellent post- operative outcomes with much comfort, more stableas well as fewer complications. So, it appears to be an effective means to treat primary pterygium surgically. JCMCTA 2020 ; 31 (1) : 42-47